Relationship of expression of HER 2 protein according to histological type tumors by lauren in gastric cancer - Spahić, Amir; Jakovljević, Branislava (International Journal of Research in Medical Sciences, 2017)
Background: Gastric cancer, by the definition of World Health Organization (WHO), is a malignant epithelial tumor of mucosa of the stomach with glandular differentiation. Objective of this Scientific paper was to maintain the relation of expression of HER2 protein and hystological type of cancer according to Lauren in gastric cancer. Methods: In this research, archival samples of tissues of gastric cancer are used from 60 patients that have been obtained after subttotal or total Gastrectomy with a regional lymphadenectomy of lymph nodes. The most representative tissue samples of gastric cancer tissues are selected by the standard hematoxylin-eosin staining method which are cut again by using a microtome and treated by immunohistochemistrical technique with antibody on the HER2 according to the protocol of the producer and then evaluated by light-microscopic and again evaluated by a modified system of scoring the HER2 positivity of surgical resections. In the data processing, descriptive statistics and nonparametric test of significance respectively. Chi square test and one sample T-test, and also correlation tests respectively Pearson test of correlation. Results: Statistical analysis of expression of HER2 protein according to hystological type of gastric cancer done by chi-square test, does not show significant relation between these two variables (x2=4,900). Analysis by using one sample T-test does not show statistical significance (t=1.1880), and analysis by using Pearson test of correlation shows negative correlation that is not statistically significant (r= -0.029) between these two tested parameters. Conclusions: Expression of HER2 protein by using an univariate statistical method according to Pearson has shown a negligible negative correlation without statistical significance according to histological type by Lauren.